2019
DOI: 10.2147/pgpm.s179152
|View full text |Cite
|
Sign up to set email alerts
|

<p>Update on the pharmacogenomics of pain management</p>

Abstract: Pharmacogenomics is the study of genetic variants that impact drug effects through changes in a drug’s pharmacokinetics and pharmacodynamics. Pharmacogenomics is being integrated into clinical pain management practice because variants in individual genes can be predictive of how a patient may respond to a drug treatment. Pain is subjective and is considered challenging to treat. Furthermore, pain patients do not respond to treatments in the same way, which makes it hard to issue a consistent treatment regimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 108 publications
(146 reference statements)
0
39
0
3
Order By: Relevance
“…In one study of 60 adult patients with cancer receiving transdermal fentanyl, showed that polymorphisms in the gene ABCB1 could lead to significant changes in fentanyl plasma concentrations, with the ABCB1 1236TT variant being associated with a lower need for rescue medication. To date there have been no statistically significant findings for fentanyl-related adverse effects, in the previous study or current body of literature [31,32].…”
Section: Pain Medication Opioid Analgesics and Non-steroidal Antimentioning
confidence: 99%
See 2 more Smart Citations
“…In one study of 60 adult patients with cancer receiving transdermal fentanyl, showed that polymorphisms in the gene ABCB1 could lead to significant changes in fentanyl plasma concentrations, with the ABCB1 1236TT variant being associated with a lower need for rescue medication. To date there have been no statistically significant findings for fentanyl-related adverse effects, in the previous study or current body of literature [31,32].…”
Section: Pain Medication Opioid Analgesics and Non-steroidal Antimentioning
confidence: 99%
“…Genotypes related to morphine’s ability to treat pain, such as the GG genotype for OPRM1 , may help inform appropriate dose selection. In one study, patients with the GG genotype often require higher daily doses of morphine to achieve appropriate levels of analgesia, in comparison to the wild-type A allele (225 + 143 mg/day vs. 97 + 89 mg/day in those with the A allele for OPRM1 , p = 0.006) [31,32,93]. More than 100 variants of the receptor gene ( OPRM1 ) have been identified [113].…”
Section: Enzymes Involved In Drug Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…1 These drugs also exhibit extensive pharmacogenomic variability in the metabolism. 4 They are all metabolized through CYP2D6 to active metabolites, which have significant pharmacokinetic and pharmacodynamics differences, potential for toxicity, and potency at the muopioid receptor greater than the parent drugs. People with CYP2D6 UM (ultrarapid) metabolic phenotype may be at greater risk for overdose due to the rapid metabolism of hydrocodone, oxycodone, or tramadol to more active/potent metabolites than their peers with (poor) PM, (intermediate) IM, or (extensive) EM metabolic phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…People with CYP2D6 UM (ultrarapid) metabolic phenotype may be at greater risk for overdose due to the rapid metabolism of hydrocodone, oxycodone, or tramadol to more active/potent metabolites than their peers with (poor) PM, (intermediate) IM, or (extensive) EM metabolic phenotypes. 4 CYP2D6 ultrarapid metabolizer (UM) phenotype occurs in 3.08% of the European population and 5.51% in the American population. 5 In contrast, one recent study found 28% of patients prescribed an opioid had the UM phenotype and those patients were twice as likely to have adverse effects (20%) (vomiting, nausea, rash, itching, throat swelling, or other adverse effects that did not include overdose) compared to patients with extensive metabolizer (EM) or intermediate metabolizer (IM) phenotype who experienced less side-effects (12%).…”
Section: Introductionmentioning
confidence: 99%